Embodied agency through soft skills development in dance - Houston, Sara (Frontiers in Cognition, 2024)
The fluidity, adaptability and complexity of a dancer's movement are often used as examples of how dance at a level of mastery is embodied. The freedom this gives the dancer to choose what and how they move is enjoyed at a subconscious level, with often tacit knowledge driving the artistic and technical brilliance. The topic of embodied agency in dance becomes more complicated when examining dance for the older person who has had little training. Embodiment is not straight forward, particularly if one examines dancing for the older adult with a neurodegenerative condition, which disrupts cognition and physical movement. Yet, as I argue, embodied agency is a key vision for socially engaged dance practices, particularly using improvisation. In the paper I examine how centring the amateur older dancer with a neurological condition means looking again at embodied agency and what it could mean in this context, as well as what the conditions are that might make it work. The paper takes the example of Dance Well, a group of community dancers in Italy that accommodates people with Parkinson's and others, including those seeking asylum. With this example I draw upon ideas from research I co-led (Empowering Dance, 2022) to name some of the tacit soft skills -such as empathy and understanding and appreciating difference -developed through Dance Well's engagement with the local community, which, I now suggest, led to a process of embodied agency. I argue that in identifying this anoetic knowing (Dewey 2011), it is clear that embodied agency is not just about mastery of movement, but about important relational skills that are embodied and practised through dancing, even by those with little formal dance training. I argue that moving together whilst embodying soft skill qualities may nurture an environment that could enable the transformation of relationships between those dancing and contribute to the creation of an important and meaningful activity within the community. In this way, the paper outlines ideas on how embodied agency through dancing may contribute to a vision of social justice and a characterisation of embodiment that emphasises the recognition of each other's humanity.